Seasonal variations of the chemical composition of Brazilian propolis - Bankova, V; Boudourova-Krasteva, G.; Popov, S.; Sforcin, J. M.; Funari, SRC (Elsevier B.V., 1998)
The seasonal variations in the chemical composition of Brazilian propolis, collected by two bee subspecies, Africanized Apis mellifera and European Apis mellifera ligustica, have been investigated by GC and CC-MS. The main components of the samples were phenolic compounds, especially cinnamic acid derivatives, the only exception being the autumn sample from Apis mellifera ligustica, where diterpenes predominated. In propolis from both subspecies, diterpenes appeared in summer and reached maximum percentage in autumn, but were absent during the other seasons. The results obtained indicated that both bee subspecies collect propolis from among the same group of plants, and that there are at least two important plant sources, but these remain unidentified. (C) Inra/DIB/AGIB/Elsevier, Paris.
Keywords: propolis; chemical composition; phenolics; diterpenes; GC-MS; Brazil; seasonal variation